Ambient air pollution triggers wheezing symptoms in infants. Issue 8 (11th February 2008) - Andersen, Z J; Loft, S; Ketzel, M; Stage, M; Scheike, T; Hermansen, M N; Bisgaard, H
Abstract : Background: There is limited evidence for the role of air pollution in the development and triggering of wheezing symptoms in young children. A study was undertaken to examine the effect of exposure to air pollution on wheezing symptoms in children under the age of 3 years with genetic susceptibility to asthma. Methods: Daily recordings of symptoms were obtained for 205 children participating in the birth cohort study Copenhagen Prospective Study on Asthma in Children and living in Copenhagen for the first 3 years of life. Daily air pollution levels for particulate matter <10 μm in diameter (PM10 ) and the concentrations of ultrafine particles, nitrogen dioxide (NO2 ), nitrogen oxide (NOx ) and carbon monoxide (CO) were available from a central background monitoring station in Copenhagen. The association between incident wheezing symptoms and air pollution on the concurrent and previous 4 days was estimated by a logistic regression model (generalised estimating equation) controlling for temperature, season, gender, age, exposure to smoking and paternal history of asthma. Results: Significant positive associations were found between concentrations of PM10, NO2, NOx, CO and wheezing symptoms in infants (aged 0–1 year) with a delay of 3–4 days. Only the traffic-related gases (NO2, NOx ) showed significant effects throughout the 3 years of life, albeit attenuating after the age of 1 year. Conclusions: Air pollution related to traffic is significantly associated with triggering of wheezing symptoms in the first 3 years of life.